POTENSI KONFLIK PERNIKAHAN TANPA ADAT BATAK TOBA (STUDI DESKRIPTIF PADA PASANGAN YANG MENIKAH TANPA ADAT BATAK TOBA DI DESA SUKAJADI KECAMATAN BUKIT BATU KABUPATEN BENGKALIS) - Ospriani, Ria; Yusuf, Yusmar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This research was carried out at Sukajadi Village, Bukit Batu district, Bengkalis Regency. The purpose of this study is to find out what factors of Christianity are the background of couples who marry without traditional ceremonies. The topic of this research focus is to know the background of the life description of married couples without custom in their socialization lives in the family and Batak community. The sample in this study amounted to 5 people. The author uses qualitative methods and uses Sampling quota retrieval techniques. Data instruments are observation, interviews and documentation. From the research conducted, the author found that married couples who are married without using custom are due to economic factors, different beliefs, cannot be blessed by parents. There are also many couples who are married without Batak customs who consider it true without being treated as a matter of course, but this assumption is strongly denied by traditional Batak leaders, because until whenever the Batak people were very thick in their customs, he also said that he died later must be dealt with, if the marriage does not use custom will affect the child who is going to get married where if his parents are not subjected to his child it is also not allowed to invite parents at a traditional party, so until whenever he said Batak people must understand about the ritual. For those who are charismatic, the Batak tradition is very contrary to their teachings because the charismatic church only believes in getting that blessing by just accepting the blessing of the church, not from its traditional system, most of the people who have charismatic beliefs do not know civilization. Keywords: Indigenous Marriage, Conflict, Culture